A Microporous Co(II)‐Based 3‐D Metal Organic Framework Built from Magnetic Infinite Rod‐Shaped Secondary Building Units. Issue 38 (25th September 2019) - Kourtellaris, Andreas; Moushi, Eleni E.; Spanopoulos, Ioannis; Trikalitis, Pantelis N.; Pissas, Michael; Papaefstathiou, Giannis S.; Sanakis, Yiannis; Tasiopoulos, Anastasios J.
Abstract : The synthesis and characterization of [Co5 (INA)3 (HCOO)7 (DMF)(H2 O)]· 2DMF· 4H2 O∞ (INA – = the anion of isonicotinic acid) denoted asCo5‐INA· 2DMF· 4H2 O is reported. The compound was isolated from the reaction of Co(NO3 )2 · 6H2 O with HINA in the presence of HCOOH in N, N‐dimethylformamide (DMF) at 100 °C. It exhibits a rigid 3‐D porous structure based on Co5 repeating units which are linked through carboxylate ligands (from HCOO – and INA – ) to form an infinite rod‐shaped secondary building unit (SBU). The rods are connected through isonicotinate ligands to produce a unique (3, 3, 4, 4, 4‐coordinated) 5‐nodal 3D network with point symbol (4.5.6.7 2 .9)(4.5.6 2 .7.8)(4.5.7)2 (5.6 2 .7 3 ). Gas sorption studies revealed thatCo5‐INA displays a microporous structure with BET area 264.5 m 2 g –1 and CO2 uptake of 1.96/1.29 mmol· g –1 at 273/298 K (1 bar), respectively. Magnetism studies revealed thatCo5‐INA displays spin canting behavior with a spin glass relaxation process at ca. 5.0 K. Abstract : A MOF denoted asCo5‐INA based on the isonicotinate ligand and consisting of a novel Co5 repeating unit and an unprecedented zig‐zag rod secondary building unit is presented.Co5‐INA exhibits a rigid 3‐D porous structure and a magnetic phase transition at ca. 5. 0 K.